Comparison of reliabilities and validity between AR based motion capture system and physical therapist : preliminary study - et. al., JaeHo Yu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
AR based motion capture system(ABMCS) is a program that provides multiple practical type of training exercises and rehabilitation programs and with an included motion capture sensor, it is an alternative method for range of motion measurement. The present study aimed to compare the difference between the augmented reality-based measurement tool using motion capture system and the therapist's measurement using goniometer for measuring the range of motion (ROM) of the joint. Three ROM motions on the upper extremity (shoulder abduction, flexion, external rotation), two on lower extremity (knee extension, hip abduction) and trunk flexion were measured. The measurement was done simultaneously to avoid errors and the results were recorded in degrees. Excepting shoulder external rotation and trunk flexion, the result was similar and not significant difference between AR based motion capture system compared to the goniometer. A measurement tool based on augmented reality using AR based motion capture system can be expected to have a good prospect as an evaluation tool if the evaluation is conducted in the way subject and the target join is inside the focus of the sensor.